OVERVIEW OF TELEDIAGNOSIS IN BRAZIL FROM 2016 TO THE FIRST WAVE OF THE COVID-19 PANDEMIC - Jandre Reis, Felipe José (2023)
Telemedicine, including telediagnosis, must be recognized as an alternative to overcome geographical barriers, provide patients with access to health care and ensure continuity of follow-up. The aim of this study was to quantify the number of telediagnosis from 2016 to the first wave of the COVID-19 pandemic in Brazil. This study is a secondary analysis of data from the Brazilian Ministry of Health. The main outcomes were: total number of telediagnoses performed, mean time to telediagnosis notification; the distribution of states and municipalities with the highest number of telediagnosis and the health specialties that performed telediagnosis the most. A total of 4,010,087 telediagnoses with irregular distribution were identified (59.5% in Minas Gerais, 29.4% in Santa Catarina, 3.3% in Ceará and 2.2% in Bahia). At the beginning of COVID cases in Brazil, there was a reduction in telediagnosis, being 12% in February, 41% in March, 81% in April, 80% in May and 76% in June. Brazil presented an irregular distribution of telediagnoses in the different states. During the first wave of the COVID-19 pandemic, a significant reduction in the number of telediagnoses was observed.